Software engineering with Microsoft Visual Studio Team System - Guckenheimer, Sam, 1956- (Addison Wesley, 2006)
Software Engineering with Microsoft Visual Studio Team System is written for any software team that is considering running a software project using Visual Studio Team System (VSTS), or evaluating modern software development practices for its use. It is about the value-up paradigm of software development, which forms the basis of VSTS: its guiding ideas, why they are presented in certain ways, and how they fit into the process of managing the software lifecycle. This book is the next best thing to having an onsite coach who can lead the team through a consistent set of processes. Sam Guckenheimer has been the chief customer advocate for VSTS, responsible for its end-to-end external design. He has written this book as a framework for thinking about software projects in a way that can be directly tooled by VSTS. It presents essential theory and practical examples to describe a realistic process for IT projects. Readers will learn what they need to know to get started with VSTS, including The role of the value-up paradigm (versus work-down) in the software development lifecycle, and the meanings and importance of "flow" The use of MSF for Agile Software Development and MSF for CMMI Process Improvement Work items for planning and managing backlog in VSTS Multidimensional, daily metrics to maintain project flow and enable estimation Creating requirements using personas and scenarios Project management with iterations, trustworthy transparency, and friction-free metrics Architectural design using a value-up view, service-oriented architecture, constraints, and qualities of service Development with unit tests, code coverage, profiling, and build automation Testing for customer value with scenarios, qualities of service, configurations, data, exploration, and metrics Effective bug reporting and bug assessment Troubleshooting a project: recognizing and correcting common pitfalls and antipatterns This is a book that any team using or considering VSTS should read. "This is first and foremost a book about software engineering. In discussing flash points such as planning, documentation, governance, auditability, and organization, Sam presents the case for both agile and more formal practices, as well as describing the optimal conditions for each. Even though the material is presented in the context of VSTS, the guidance is universal." -Dr. Bill Curtis chief process officer, Borland Software Corporation "Sam Guckenheimer ushers in the era of trustworthy tran...